Isolation, Identification, and Characterization of a New Highly Pathogenic Field Isolate of Mycobacterium avium spp. avium - Zhu, Liangquan; Peng, Yong; Ye, Junxian; Wang, Tuanjie; Bian, Zengjie; Qin, Yuming; Zhang, He; Ding, Jiabo (Frontiers in Veterinary Science, 2018)
Avian tuberculosis is a chronic, contagious zoonotic disease affecting birds, mammals and humans. The disease is most often caused by Mycobacterium avium subsp. avium (MAA). Strain resources are important for research on avian tuberculosis and vaccine development. However, there has been little reported about the newly identified MAA strain in recent years in China. In this study, a new strain was isolated from a fowl with symptoms of avian tuberculosis by bacterial culture. The isolated strain was identified to be MAA by culture, staining, and biochemical and genetic analysis, except for different colony morphology. The isolated strain was Ziehl-Zeelsen staining positive, resistant to p-nitrobenzoic acid, and negative for niacin production, Tween-80 hydrolysis, heat stable catalase and nitrate production. The strain had the DnaJ gene, IS1245 and IS901, as well. Serum agglutination indicated that the MAA strain was of serotype 1. The MAA strain showed strong virulence via mortality in rabbits and chickens. The prepared tuberculin of the MAA strain had similar potency compared to the MAA reference strain and standard tuberculin via a tuberculin skin test. Our studies suggested that this MAA strain tends to be a novel sub-type, which might enrich the strain resource of avian tuberculosis.